European Court of Justice decision in Coman case and its implications in the same-sex spouses matter - Spirchez Georgeta-Bianca (Bulletin of the Transilvania University of Brasov, series VII: Social Sciences. Law. vol.14(63) Special issue, 2022)
Romania is still showing a strong resistance towards the spectacular changes in the way the family is currently regulated by the legal systems of other EU Member States. Under such conditions, through this study we are concerned about the issue of the recognition, by the Romanian State, of a marriage validly concluded abroad, between a Union citizen and his spouse of the same sex, who is a third country national. Our analysis starts from the principles developed by the European Union Court of Justice, in Coman case, a decision that brought back into the debate issues such as the right to family life and the right to freedom of movement, viewed from the perspective of the discrimination prohibition on grounds of sexual orientation
Keywords: same-sex spouses; family member; right of residence; freedom of movement